2007
DOI: 10.1074/jbc.m705089200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Inhibitor of Differentiation-1 (ID-1) Binding Partner, Caveolin-1, and Its Role in Epithelial-Mesenchymal Transition and Resistance to Apoptosis in Prostate Cancer Cells

Abstract: Recently, ID-1 (inhibitor of differentiation/DNA binding) is suggested as an oncogene and is reported to promote cell proliferation, invasion, and survival in several types of human cancer cells through multiple signaling pathways. However, how Id-1 interacts with these pathways and the immediate downstream effectors of the Id-1 protein are not known. In this study, using a yeast two-hybrid screening technique, we identified a novel Id-1-interacting protein, caveolin-1 (Cav-1), a cell membrane protein, and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 41 publications
6
63
1
Order By: Relevance
“…Activation of the Akt-mediated Wnt/TCF pathway by Id-1 overexpression in MCF7 cells A recent study showed that Id-1-induced Akt-mediated EMT and enhanced cell migration (Zhang et al, 2007). Consistently, our data showed Id-1-induced Akt activation, GSK-3b phosphorylation and b-catenin and cyclin D1 expressions (Figure 1a).…”
Section: Id-1 Inhibits Pten Transcription Through P53 Downregulationsupporting
confidence: 90%
See 3 more Smart Citations
“…Activation of the Akt-mediated Wnt/TCF pathway by Id-1 overexpression in MCF7 cells A recent study showed that Id-1-induced Akt-mediated EMT and enhanced cell migration (Zhang et al, 2007). Consistently, our data showed Id-1-induced Akt activation, GSK-3b phosphorylation and b-catenin and cyclin D1 expressions (Figure 1a).…”
Section: Id-1 Inhibits Pten Transcription Through P53 Downregulationsupporting
confidence: 90%
“…Recently, it was reported that Id-1 inhibits protein phosphatase 2A activity, which led to Akt dephosphorylation (Zhang et al, 2007). Here, our data provide the first evidence that Id-1 can control PTEN as a novel negative regulator that activates the Akt pathway.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Most importantly, Id-1 has been shown to promote metastasis of prostate cancer. Id-1 promotes angiogenesis through upregulation of VEGF , while it also binds to caveolin-1 to induce epithelial -mesenchymal transition in prostate cancer cells (Zhang et al, 2007a). In addition, increased expression of Id-1 is significantly associated with shorter survival of prostate cancer patients (Forootan et al, 2007).…”
mentioning
confidence: 99%